THE EFFECT OF HUMAN RESOURCE INFORMATION SYSTEMS ON EMPLOYEE PERFORMANCE - Sukanto Krisbianto (Jurnal Scientia, 2023)
This research was conducted to determine the effect of HR information systems on employee performance. The method used in this study uses descriptive and verification methods. The population used is all employees of the Promenade Bandung hotel. The results of the study indicate that there is a significant effect of the HR Information System on employee performance. The research results show that the influence of HR information systems on employee performance in the very significant category is 57.1%. so that the findings in this study by following all of the Company's Operating Standards related to the steps that have been implemented by the Company will increase the influence of the human resource information system on employee performance.